Textual Analysis of Selected Online Messages on 2019-2020 Coronavirus Pandemic - Udende, Patrick; Longs, Joy Nanko (Unisia, 2025)
In response to the emergence of corona virus in 2019, researchers have demonstrated sustained interest in conducting studies on the emerging virus. Prompted to explore online perspectives on the pandemic, a qualitative study was conducted. The aim was to understand the pattern of messages people post online. Four online platforms were purposively selected namely; Facebook, Channels Television, Pulse Nigeria, and Punch Newspapers between February, 2020 and October, 2020. In the same vein, 18 posts were purposively selected from these platforms and the interpretative approach which thrust is to gain insight into the specific meanings and behaviours experienced in the context of COVID-19 pandemic was used to analyze the data. Findings indicate that while some messages are pessimistic and threatening, others are laced with aura of optimism. Findings further indicate a varied pattern including misleading posts, socio-economic consequences, anxiety, humour, enlightenment, remedial approach and preventive measures. The study concludes that online platforms are irreplaceable means of sharing messages about issues of global health concern especially now that the platforms have become part of human existence.